Penggunaan Negative Reinforcement sebagai Model Pola Asuh dalam Meningkatkan Perilaku Disiplin Anak Usia Dini di TPQ Daarul Qur’an Wonosari (Jurusan Bimbingan dan Konseling Islam, 2021)
The use of Negative Reinforcement as a Model of Parenting in Improving Early Chilhood Discipline Behavior in TPQ Daarul Qur’an Wonosari Boalemo Gorontalo.The focus of this research are: (1) How is the process of using negative reinforcement as a parenting model in improving early chilhood disciplinary behavior in TPQ Daarul Qur’an Wonosari Boalemo Gorontalo? (2) What are the results of using negative reinforcement as an parenting model in improving early chilhood disciplinary in the TPQ Daarul Qur’an Wonosari Boalemo Gorontalo? To answer the problems raised in this study, researchers usedqualitative research methods, with the type of case study research. Qualitative research data were obtained through interview techniques, participant observation, and documentation.In this study is concluded that, (1) the process of using negative reinforcement through stages according to theory, using the type of avoidance and escape operant conditioning, provides negative stimuli to early chilhood so that it causes a response to children’s behavior and produces a consequence that has a lasting effect long, namely discipline.(2) The result of the use of negative reinforcement is that children begin to get used to disciplined behavior, have an orderly and directed personality.